ANALISIS PENGARUH BELANJA PEMERINTAH, IPM, DAN INVESTASI DALAM NEGERI TERHADAP PERTUMBUHAN EKONOMI PROVINSI PAPUA - -, Gharnis Intan Krasmanik B.P; -, Candra Fajri Ananda (Journal of Development Economic and Social Studies, 2024)
Economic growth is a benchmark for analysis of a region's development. So it is necessary to pay attention to the determinants of economic growth. Papua is a case study in this analysis because the level of economic growth is in the high category, in addition to the human development index remaining low in the last ten years. This research aims to analyze the influence of government spending according to function, human development index and investment on economic growth in Papua Province in 2011-2019. The type of data used is panel data from 29 districts/cities for eight years using the panel data regression analysis method. The results of this research show that government spending has different results for each type of government function spending. It was found that education spending and economic spending had no influence on economic growth, but the opposite was true for health spending. Apart from that, the human development and investment index explained through PMTB also has an influence on economic growth. These findings could have implications for the government in deciding policies for allocating government spending, especially for education and economic spending functions, which are still not efficient in stimulating economic growth in the Papua region.